Local veterinary knowledge - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Ethnoveterinary practices research and development Edited by J O Gefu, P A Abdu & C B Alawa, National Animal Production Research Institute, Ahmadu Bello University, Nigeria. 2000. 166 pp. ISBN 978 2364 26 8 US$15 Euro 17.80